Role of CXR and HRCT in diagnosing COVID-19, a descriptive cross-sectional study, at a tertiary care hospital in Pakistan - Hina Hanif Mughal, Madiha Maryam Azam, Faryal Azher, Nasir Khan, Sadia Chaudhry, Hina Sattar (Journal of Rawalpindi Medical College, 2021)
ABSTRACT Objectives: Objectives of this study are to do the analysis of chest X-ray and High-resolution CT scan findings in patients who are clinical suspects of COVID-19 infection. The other objective is to classify the radiological findings in mild, moderate or severe diseases according to BSTI criteria for chest X-ray and CTSS for high-resolution CT scan. Methods: This is a cross-sectional descriptive study. A group of 50 patients who were clinically suspected cases of COVID-19 infection, presented to Corona flu filter clinic of Holy Family Hospital (HFH) or admitted to corona isolation wards were included. The time duration of the study was from 15 May 2020 to 15 June 2020. Patients labelled as clinically suspected cases were having positive contact with confirmed positive (based upon positive PCR) patients. Recent travel history from the area having an outbreak. They were having clinical signs/symptoms of fever, cough, and shortness of breath, lethargy and loss of sense of smell or taste. CXR and HRCT was the investigation of choice for all the 50 patients. I also did PCR to make a correlation with the other two tests. All radiological findings were analyzed based upon Fleischner society glossary of terms for thoracic imaging. Two radiologists then assessed CXRs findings based upon BSTI criteria. They marked those CXR findings as low, moderate and high probability for COVID-19 infection. HRCT findings were analyzed using CT-SS, and researchers labelled outcomes as mild, moderate and severe disease. Results: Out of 50 patients, 33(66%) were males, and 17(34%) were females. Mean age was 51 with ages ranging from 30-72 years. Presenting complaints were fever in 42(84%) patients, cough in 37(74%), lethargy in 33(66%), shortness of breath in 41(82%) and loss of sense of smell and taste in 21(42%) patients. Out of these 50, 32(72%) were having positive PCR for COVID-19 infection. On CXR 5(10%) patients showed classic findings which were highly probable for COVID-19. 19(38%) patients showed intermediate results for COVID-19, 7(14%) patients had a low probability of COVID-19 infection on CXRS. Out of 50, 19(38%), patients showed normal CXR with no evidence of COVID-19 infection. We did HRCT of the same patients on the same day; it showed 21(42%)patients with mild disease,23(46%)patients with moderate disease and 6(12%)patients with the severe disease according to CTSI.HRCT of 3(6%)patients was ok with no evidence of illness in bilateral lungs. Conclusion: The role of radiology is crucial in the diagnosis of this viral illness. CXR, with its ability to detect changes of COVID-19 in lungs, should be used as a first-line imaging modality in clinically suspected patients. Moreover, it should also be used for follow up of patients with COVID-19. HRCT is very sensitive in the diagnosis of COVID-19 infection in its milder forms. Due to lack of its widespread availability in countries with inadequate medical facilities, it was not the primary imaging tool/screening tool. Due to risk of infection to radiological staff as well as non-covid-19 patients due to surface contact, due to reduced infection control issues, due to increased burden of ionizing radiations in patients. All these factors limit the role of HRCT as a primary imaging modality for COVID-19 infection